1984
DOI: 10.1139/m84-236
|View full text |Cite
|
Sign up to set email alerts
|

Hyphal interactions between a mycoparasite, Pythium nunn, and several soil fungi

Abstract: The modes of hyphal interaction between a mycoparasite, Pythium nunn, and several soil fungi were studied by both phase-contrast and scanning-electron microscopy. In the zone of interaction, Pyth. nunn massively coiled around and subsequently lysed hyphae of Pyth. ultimum and Pyth. vexans. In contrast, Pyth. nunn penetrated and eventually parasitized hyphae of Rhizoctonia solani, Pyth. aphanidermatum, Phytophthora parasitica, and Phyto. cinnamomi by forming appressoriumlike structures. However, Pyth. nunn was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
2

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 0 publications
2
17
0
2
Order By: Relevance
“…Nelson et al 1988;Paulitz and Bélanger 2001). The biological control agents P. oligandrum (Vesely 1977) and P. nunn (Lifshitz et al 1984) were discovered and have been shown to control Pythium diseases (Martin and Loper 1999). This is a rare situation in biological control in that the control agent is from the same genus as the pathogen or pest it is controlling.…”
Section: Biological Controlmentioning
confidence: 99%
“…Nelson et al 1988;Paulitz and Bélanger 2001). The biological control agents P. oligandrum (Vesely 1977) and P. nunn (Lifshitz et al 1984) were discovered and have been shown to control Pythium diseases (Martin and Loper 1999). This is a rare situation in biological control in that the control agent is from the same genus as the pathogen or pest it is controlling.…”
Section: Biological Controlmentioning
confidence: 99%
“…These phenomena are consistent with previous observations of hyphal interactions between P. nunn and P. ultimum var. ultimum (Adams 1990;Lifshitz et al 1984a). …”
Section: Hyphal Interactionmentioning
confidence: 99%
“…Pythium nunn Lifshitz, Stanghellini & Baker is a potential biocontrol agent first recorded from a grassland soil in Colorado, USA (Lifshitz et al 1984a). This species, which has never been recorded as a plant pathogen (Lifshitz et al 1984b, c), efficiently suppresses pre-emergence damping off of cucumber seedlings caused by P. ultimum Trow var.…”
Section: Introductionmentioning
confidence: 99%
“…Rather an antagonist, P. nunn (Lifshitz et al 1984c), increased in population density whereas Pythium ultimum was reduced to low levels after five weekly applications of bean meal (Lifshitz et al 1984b). Rampant mycoparasitism was observed by use of SEM and light microscopy in vitro (Lifshitz et al 1984a) involving hosts like Pythium spp., Phytophthora spp., and R. solani.…”
mentioning
confidence: 99%
“…Such events appear to be related to those demonstrated in plant parasitic interactions. In a number of recent reviews (Baker 1987, Chet 1986, Elad & Misaghi 1985, attention has been directed primarily toward description and biochemical interactions of Trichoderma spp, When a mycoparasite is grown with its host in dual culture, atypical branching by hyphae of the antagonist may occur and there is trophic growth toward the host , Lifshitz et al 1984a). The biochemical basis for this is not understood but there is reasonable speculation by investigators that trophic responses are induced by nutrient gradients arising from the host.…”
mentioning
confidence: 99%